The Students’ Motivation and Grit As Predictors on Reading Achievement: A Correlational Study on the Sixth Semester Students of English Study Program Tanjungpura University in Academic Year 2021/2022 - Tiabarte, Aulyahaq (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The objective of this study is to examine the relationship between students' reading motivation and their reading achievement, as well as the relationship between students' grit and their reading achievement. Additionally, this study aims to explore the interplay among students' motivation, grit, and reading achievement. In this research, the researcher employed two types of motivation: intrinsic and extrinsic, and two types of grit: consistency of interest and perseverance of effort. This research is a quantitative correlational study with the population consisting of fifty-five students in the sixth semester of the S1 English Study Program Regular A of Tanjungpura University in Pontianak in the academic year of 2021/2022 who already took two reading courses (intensive reading and reading skill development) on their past semesters. Data were collected using questionnaires. The questionnaires consisted of 40 reading motivation items and 8 grit items on a 4 Likert scale ranging from “Very Different from Me” to “A lot Like Me”. Based on the research findings, there is a correlation with reading achievement (r= 0.551). There exists a positive connection (r=0.748) among grit and reading achievement. Additionally, it is noteworthy that there exists a good association between an individual's motivation to read and their level of perseverance and passion towards achieving success in reading (r=0.758). The study's major findings indicate a favorable correlation between the motivation and grit of great performers. There exists a positive correlation between an individual's level of motivation and grit and their level of achievement.